Adsorption properties of porous silicon - Teodor Gotszalk; Ivo W. Rangelow; Piotr Grabiec (Journal of Telecommunications and Information Technology, 2001)
Porous silicon shows some interesting features for micromechanical applications. Some applications make use of its high surface-to-volume ratio. A capacitive gas or humidity sensor using the adsorption of gases on the porous surface can be easily fabricated. However an opportunity for more sensitive device is given by micromechanical structure. In this paper we report on the piezoresistive cantilever beam structure with porous silicon adsorbing spot as a gas sensor.